Impact Of Fertilizer Subsidy Policy On Fertilizer Use In Su-korambi Sub-District, Jember - Rosita, Rosita; Prayuningsih, Henik; Muliasari, Risa Martha (International Applied Science, 2024)
Fertilizer subsidy is one of the government's efforts so that farmers can access fertilizer needs for their farms at more affordable prices, so that it is expected to encourage increased agricultural production in order to achieve food security. Healthy rice crop is a process in rice cultivation that prioritizes the use of natural ingredients that are environmentally friendly in the sense that they remain effective but still maintain productivity, production and quality of agricultural products. This study aims to determine the comparison of whether the reduction of subsidized fertilizer policy will affect the use of fertilizers in Sukorambi Jember District. Sampling using quota sampling method as many as 40 samples, consisting of 20 farmer group members who apply healthy agriculture and 20 farmer group members who apply conventional agriculture. The results showed that the comparison of the use of organic fertilizer before and after the change in fertilizer subsidy policy increased. The use of urea and NPK fertilizers in healthy rice decreased, but the use of KCL and ZA fertilizers remained. While the use of urea, NPK, and KCL fertilizers on conventional rice increased, but the use of ZA fertilizer remained.